Assessing toluene biodegradation under temporally varying redox conditions in a fractured bedrock aquifer using stable isotope methods. (15th November 2019) - Wanner, Philipp; Aravena, Ramon; Fernandes, Jeremy; BenIsrael, Michael; Haack, Elizabeth A.; Tsao, David T.; Dunfield, Kari E.; Parker, Beth L.
Abstract: In complex hydrogeological settings little is known about the extent of temporally varying redox conditions and their effect on aromatic hydrocarbon biodegradation. This study aims to assess the impact of changing redox conditions over time on aromatic hydrocarbon biodegradation in a fractured bedrock aquifer using stable isotope methods. To that end, four snapshots of highly spatio-temporally resolved contaminant and redox sensitive species concentrations, as well as stable isotope ratio profiles, were determined over a two-years time period in summer 2016, spring 2017, fall 2017 and summer 2018 in a toluene contaminated fractured bedrock aquifer. The concentration profiles of redox sensitive species and stable isotope ratio profiles for dissolved inorganic carbon (DIC) and sulfate (δ 13 CDIC, δ 34 SSO4, δ 18 OSO4 ) revealed that the aquifer alternates between oxidising (spring 2017/summer 2018) and reducing conditions (summer 2016/fall 2017). This alternation was attributed to a stronger aquifer recharge with oxygen-rich meltwater in spring 2017/summer 2018 compared to summer 2016/fall 2017. The temporally varying redox conditions coincided with various extents of toluene biodegradation revealed by the different magnitude of heavy carbon ( 13 C) and hydrogen ( 2 H) isotope enrichment in toluene. This indicated that the extent of toluene biodegradation and its contribution to plume attenuation was controlled by the temporally changing redox conditions. The highest toluene biodegradation was observed in summer 2016, followed by spring 2017 and fall 2017, whereby these temporal changes in biodegradation occurred throughout the whole plume. Thus, under temporally varying recharge conditions both the core and the fringe of a contaminant plume can be replenished with terminal electron acceptors causing biodegradation in the whole plume and not only at its distal end as previously suggested by the plume fringe concept. Overall, this study highlights the importance of highly temporally resolved groundwater monitoring to capture temporally varying biodegradation rates and to accurately predict biodegradation-induced contaminant attenuation in fractured bedrock aquifers. Graphical abstract: Image 1 Highlights: Changing recharge conditions cause temporal variation of aquifer redox conditions. Impact of varying redox conditions on toluene degradation shown by isotope ratios. Evaluation if plume reaches steady state conditions under changing redox conditions. Illustration of importance of highly temporally resolved groundwater monitoring.